Cover Picture: Self‐Assembling All‐Enzyme Hydrogels for Flow Biocatalysis (Angew. Chem. Int. Ed. 52/2018). Issue 52 (28th November 2018) - Peschke, Theo; Bitterwolf, Patrick; Gallus, Sabrina; Hu, Yong; Oelschlaeger, Claude; Willenbacher, Norbert; Rabe, Kersten S.; Niemeyer, Christof M.
Abstract : The next wave of biocatalysis will be enabled by machine‐assisted flow processes that require tailor‐made materials to achieve efficient product conversion. In their Communication on page 17028 ff., C. M. Niemeyer and co‐workers describe self‐assembling all‐enzyme hydrogels that are made from two cooperating enzymes and can be produced in macroscopic quantities (blue background image). Mounted in microfluidic reactors, the gels show excellent stereoselectivity with near quantitative conversion in the reduction of ketones along with extraordinary high turnover of expensive cofactors.